Legal Responsibility for Environmental Damage Caused by Russian and Ukrainan Wars: International Humanitarian and Criminal Law Perspectives - Romdoni, Rafi Nasrulloh Muhammad (Universitas Kuningan, 2023)
Not only inflicted human casualities, the war between Russia and Ukraine, also injured the environment. Russia's discriminating attacks on essential objects such as gas, energy, oil, and mining infrastructure become the most significant root cause. UNEP affirmed that the attacks resulted in widespread water, soil, and air pollution, as well as a significant deterioration in Ukraine's ecosystem stability. Accordingly, the study intends to examine the framework of international humanitarian and criminal law, specifically in terms of environmental protection, as well as to analyse accountability before the International Criminal Court. The study employed a doctrinal method involving a statutory and conceptual approach. In this case, relevant legal instruments such as the 1949 Geneva Conventions and their Additional Protocols, as well as the Rome Statute, were being examined. Furthermore, the study is also certified by the evolution of legal doctrines in books, journals, and other credible sources. According to the findings, humanitarian law, which is underpinned by customary international law, protects the environment slightly better than international criminal law. In short, the state bears multiple duties for environmental damage caused by the outbreak of war. Individual accountability before the ICC, on the other hand, is being overlooked. It is due to the Rome Statute's flaws, which include vagueness in the formulation of the articles, stringent standards for proof of environmental damage, and bias in proving mens rea. As a result, improvements in the enforcement of international crimes (war crimes and related types) that cause environmental damage are urgently required.